A GIS-Based Study of the Distribution of Settlements in Roman Britain in Relation to Environmental Factors - Yao, Yikai (Transactions on Environment, Energy and Earth Sciences, 2024)
This study utilizes Geographic Information Systems (GIS) technology to conduct an analysis of the relationship between the spatial distribution of settlements during the Roman Britain period (43-410 AD) and environmental factors. This study employs the ArcGIS software to process archaeological data and integrate it with natural geographic information. A variety of spatial analysis techniques were utilized to explore the impact of multiple social and natural factors on the distribution of settlements. The research findings indicate that the majority of settlements are concentrated in the southern and central eastern regions of the British Isles, particularly in plain areas near water sources. Nucleated settlements in Roman Britain held significant economic and cultural status. There exists a strong correlation between the economic and cultural activities at these archaeological sites. Furthermore, the distribution of archaeological sites is directly associated with local ecosystem and hydrological features. A multitude of environmental factors collectively determine the distribution characteristics of archaeological sites.